Real-time path planning using a modified A* algorithm - A. Paulo Moreira (2009)
Real-Time path planning is a key issue for the performance of a mobile robot. In this paper, a modified A* algorithm that can plan in real-time the best path is presented. The suggested modifications to the A* algorithm enable it to deal with non static obstacles in an efficient way. It is shown that the proposed algorithm produces better results when used with moving obstacles.